High Preferred Orientation on c-axis of ZnO:GO Crystal Film Synthesized Under Electric Field - Rahmawati, Annisa Nur; Utami, Nabilah Putri; Safriani, Lusi; Bahtiar, Ayi; Arsyad, Wa Ode Sukmawati; Nurazizah, Euis Siti; Aprilia, Annisa (Universitas Negeri Surabaya, 2023)
ZnO nanostructures show a wide range of applications as active materials in optoelectronic devices. The unique structures in 1-dimensional (1D) in combination with other potential materials (such as graphene-based) can increase several device performances. This research aims to observe the influence of an additional electric field (induced by different voltages of ±1 kV) during the growing process of the zinc oxide (ZnO): graphene oxide (GO) crystal. The ZnO:GO layers were prepared via the self-assembly method in 2 steps; the first was seed layer preparation by dip coating technique using Zn (CH3COO)2.2H2O and 0.5 (wt%) of AlCl3 as precursor and dopant, respectively. Secondly, growing ZnO rods using Zn (NO3)2·6H2O as precursor, 0.5 (wt%) GO (dispersed in water) as dopant materials, and hexamethylenetetramine (HMTA) as complexing agent. Applying an external field during self-assembly accelerated the ZnO hexagonal wurtzite crystal formation in a vertical growth direction, increasing the aspect ratio (L/d) of ZnO:GO rods. The direction of the applied external field affected the structure and morphology of the ZnO rods, which relates to ions and seed layer surface polarity during the synthesis process. The addition of an external field during the growing process induced the orderly alignment of ZnO rods, controlling growth perpendicular to the basal plane. This research has a significant scientific impact, elucidating the methods to control the 1D morphology of the ZnO growing process, which is closely related to the surface polarity properties of a material.